2021
DOI: 10.1038/s41531-021-00202-w
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of hypertension and Parkinson’s disease

Abstract: We evaluate the association of hypertension with PD in an Asian population and performed a meta-analysis on similar studies to address the effect of hypertension on PD risk. A matched case-control study involving 1342 Chinese subjects (671 PD and 671 age and gender-matched controls (with a mean age of 63.9 ± 9.7 and 63.5 ± 9.8 years, and identical proportion of gender distribution) was conducted. Hypertension increases PD risk by 1.9 times [OR 1.86 (1.46–2.38)]. The literature search identified 618 studies ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…Parkinson’s disease (PD) is the second most common debilitating neurodegenerative disorder, with prevalence of 1% in individuals over 60 years old worldwide [ 1 , 2 ]. PD is clinically characterized by motor deficits, including bradyskinesia, resting tremor, muscle rigidity, and postural instability, and causes significant morbidity as well as decreases in psychosocial health and physical quality of life [ 3 , 4 ]. A key pathological feature of PD is the selective loss of dopaminergic (DA) neurons in the substantia nigra pars compacta.…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson’s disease (PD) is the second most common debilitating neurodegenerative disorder, with prevalence of 1% in individuals over 60 years old worldwide [ 1 , 2 ]. PD is clinically characterized by motor deficits, including bradyskinesia, resting tremor, muscle rigidity, and postural instability, and causes significant morbidity as well as decreases in psychosocial health and physical quality of life [ 3 , 4 ]. A key pathological feature of PD is the selective loss of dopaminergic (DA) neurons in the substantia nigra pars compacta.…”
Section: Introductionmentioning
confidence: 99%
“… 90 , 91 , 92 A meta‐analysis of case‐control studies by Ng and coworkers in Asian populations, showed that hypertension increases the risk of PD by 1.9 times, but there are genetic and environmental factors that may influence it because, in the Caucasian population, hypertension was found to be a protective factor of PD. 16 Autonomic dysfunction that occurs in PD is caused by a neuropathological process by abnormal deposits of α‐synuclein forming neuronal inclusions of Lewy body that are found in autonomic neurons in peripheral nerves and also in CNS, particularly in substantia nigra pars compacta (SNpc) and locus coeruleus (LC) causing neurodegeneration. 93 , 94 Shen and coworkers found that the BPV in the advanced stage of the PD group was significantly higher than in the early stage of the PD group and the normal group, also the differences between these groups in both BPV and circadian BP rhythm measurements were statistically significant, although there was no significant difference between the groups of PD with predominantly tremor or non‐tremor; This can allow BPV examination to detect the progression of a stage of PD or various abnormalities related to BP before other symptoms develop.…”
Section: Brain Aging and Blood Pressure Variability In Dementia And P...mentioning
confidence: 99%
“… 118 Another meta‐analysis by Hou and coworkers and Ng and coworkers suggests that hypertension might increase the risk of PD, specifically in the Asian population. 8 , 16 Those studies highlight the importance of early diagnosis and treatment of hypertension, which will be essential and critical for those with preclinical neurodegenerative disease. 8 , 118 The blood pressure target must also be personalized, especially in frail and very old patients.…”
Section: Management Of Hypertension In Neurodegenerative Diseasementioning
confidence: 99%
See 2 more Smart Citations